2005
DOI: 10.1177/0145721705274927
|View full text |Cite
|
Sign up to set email alerts
|

Patient Adherence Improves Glycemic Control

Abstract: Keeping more appointments and taking diabetes medications as directed were associated with substantial improvements in HbA1c. Efforts to enhance glycemic outcomes should include emphasis on these simple but critically important aspects of patient adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
220
3
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 297 publications
(250 citation statements)
references
References 77 publications
15
220
3
5
Order By: Relevance
“…Rhee et al also showed an increase of 0.12% in A1c for each missed visit. 28 These studies are consistent with our findings that 10% of patients were non-adherent to visits, and visit non-adherence was associated with worse glycemic control.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Rhee et al also showed an increase of 0.12% in A1c for each missed visit. 28 These studies are consistent with our findings that 10% of patients were non-adherent to visits, and visit non-adherence was associated with worse glycemic control.…”
Section: Discussionsupporting
confidence: 92%
“…While there are many studies evaluating the processes of care, [23][24][25][26] few studies relate these processes of care to outcomes, i.e., relating lack of testing, monitoring, or intensification with ultimate control of risk factors. 20,[27][28][29] We were unable to find any studies that evaluated visit adherence in relation to lipid or blood pressure control in diabetic adults. Two studies have evaluated the effects of appointment adherence on glycemic control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, half the patients prescribed medications for modifiable risk factors common to people with diabetes discontinue therapy within 12 months of treatment initiation (6). Poorly compliant patients miss scheduled appointments for diabetes-related monitoring and treatment (7), and this is associated with poor glucose control (7,8).…”
Section: Diabetes Care 35:1279-1284 2012mentioning
confidence: 99%
“…Karter et al (7) reported that missing scheduled medical appointments was associated with higher HbA 1c levelsda predictor of mortalitydand with poor oral medication refill adherence. Rhee et al (8) found that appointment keeping and medication adherence were each independently associated with HbA 1c levels and that those with both risk factors had the highest HbA 1c levels.…”
Section: Mortalitymentioning
confidence: 99%